2013
DOI: 10.1038/bjc.2013.716
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-risk grouping of cervical cancer patients treated with radical hysterectomy: a Korean Gynecologic Oncology Group study

Abstract: Background:In this study, we sought to identify a criterion for the intermediate-risk grouping of patients with cervical cancer who exhibit any intermediate-risk factor after radical hysterectomy.Methods:In total, 2158 patients with pathologically proven stage IB–IIA cervical cancer with any intermediate-risk factor after radical hysterectomy were randomly assigned to two groups, a development group and a validation group, at a ratio of 3 : 1 (1620 patients:538 patients). To predict recurrence, multivariate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 23 publications
1
74
1
3
Order By: Relevance
“…None of these factors has been identified to cause a significant increase in the recurrence rate by itself because sufficient power has not been obtained in statistical analyses, in part due to the interactions between these risk factors. However, when these factors are combined, the risk of recurrence increases by 15–20% …”
Section: Prognostic Risk Factors For Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…None of these factors has been identified to cause a significant increase in the recurrence rate by itself because sufficient power has not been obtained in statistical analyses, in part due to the interactions between these risk factors. However, when these factors are combined, the risk of recurrence increases by 15–20% …”
Section: Prognostic Risk Factors For Recurrencementioning
confidence: 99%
“…Ryu et al . conducted a retrospective study that aimed to define new criteria for the intermediate‐risk group of patients with cervical cancer; in that study, one‐quarter of the patients had non‐squamous cell carcinoma. They showed that four factors (adenocarcinoma, tumor size, DSI, and LVSI) were significantly associated with disease recurrence and identified a four‐factor model, in which the presence of any two factors might be useful for predicting recurrence.…”
Section: Prognostic Risk Factors For Recurrencementioning
confidence: 99%
“…In the “classic criteria” [9, 10], DSI, LVSI and tumor size ≥ 2 cm are used to stratify ESCC with an intermediate risk to envelop a recurrence: patients with two or more of these factors are candidates for adjuvant treatment; these women have a 31% probability of cancer recurrence at 3 years. Moreover, 25% of stage IB cervical cancer patients with negative lymph nodes meet the classic criteria, which indicate a limited specificity of the Classic criteria [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence rate in patients with stage IB cervical cancer who meet the Sedlis criteria was 28% without additional treatment, and an adjuvant pelvic radiotherapy achieved a reduction of 47% in the risk of recurrence in these patients [4]. Recently, a “four-factor model” has been identified, in which the presence of two of four intermediate-risk factors (tumor size ≥ 3 cm, DSI of the outer third of the cervix, LVSI, and adenocarcinoma or adenosquamous carcinoma histology) may be used to predict recurrence in ESCC patients with improved performance compared with both the “classic” and Sedlis criteria [10]. These findings indicate that additional risk factors other than the classic risk factors may be helpful to stratify patients with a recurrence risk.…”
Section: Introductionmentioning
confidence: 99%
“…21 The matching covariates were selected based on prior literature reports, known clinically prognostic factors, and availability in medical records. 22,23 Selected variables included FIGO stage, histology, induction chemotherapy status, and regional lymph nodes status (common, internal, external iliac, obturator, and presacral lymph nodes). Tumor RR was the sum of the complete response and partial response rates.…”
Section: Discussionmentioning
confidence: 99%